Global Solution and Exponential Stability for a Laminated Beam with Fourier Thermal Law (Journal of Partial Differential Equations, 2020)
This paper focuses on the long-time dynamics of a thermoelastic laminated beam modeled from the well-established Timoshenko theory. From mathematicalpoint of view, the study system consists of three hyperbolic motion equations coupledwith the parabolic equation governed by Fouriers law of heat conduction and, in consequence, does not belong to one of the classical categories of PDE. We have provedthe well-posedness and exponential stability of the system. The well-posedness is given by Hille-Yosida theorem. For the exponential decay we applied the energy methodby introducing a Lyapunov functional.